Analisa Kinerja Proteksi Gardu Induk Garuda Sakti Menggunakan Software Berbasis Visual Basic 6.0 - Shely Ayu Febriyanty; Nurhalim Nurhalim; Irsan Taufik Ali (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
PT. PLN (Persero) Garuda Sakti Substation is the center of power settings and load demand as the center of security equipment power system as well as the enter of the process of normalization of the disturbances in the territory of Pekanbaru. The goal of research to determine the quantity of fault,protection performance, and reliability of Garuda Sakti Substation. Besides, produce useful software to calculate the percentage of the quantity of fault, the precentage of protection performanceand reliability of the substation by long outages. Type of this research is qualitative descriptive. Thecalculation is done using software based Visual Basic 6.0. From the data obtained, in 2013-2014 occurred 20 times faults in Transformers and Transmission 150 kV. Protection system that works when the interruption occurs 20 times in the Garuda Sakti Substation at 2013-2014, there are five kinds of relay is: relay OVR / UVR, relay REF / SBEF, rele DF / DT, rele rele UVLS and the entire PMT 150 KV rele has a 100% reliability. Garuda Sakti Substation has good reliability because LOLPvalue in 2013 amounted to 0,234953 days per year and in 2014 of 0,09023 days per year (suitable with the standards of PLN below or equal to 3 days per year).Keywords: Fault, Protection, ENS, LOLP, Reliability Substation, Visual Basic 6.0.